Humorousness as creation and reinforcement of network society: the case of Philosophers memes - Alarcón Zayas, Violeta (2017)
With the aim of understanding humor functioning through internet and social network, we will approach memes through a determinate topic: memes about philosophers and thinkers in general since they define a very specific meaning community. We won´t adjust to a single theory, because memes´ multiplicity and their comicalness can´t be submitted by only one way of working or by specific purpose, therefore we will work from different comical concepts, from Baudelaire´s comical and caricature notions, Bajtin´s carnival grotesque concept, passing through Freud´s theories about jokes and laugh, till Bergson, Pirandello and Koestler humor definitions. From the discursive analysis we will try an explanation of how humor works in order to create, to keep and to reinforce social links.